P-75 Co-designing an anti-discrimination training programme for palliative and end of life care professionals. (19th November 2022) - Penlington, Emily; Thomas, Glyn; Ornadel, Karon
Abstract : Background: In January 2021, a social worker reported she had experienced religious discrimination from a family member of a patient. A further two recent cases of discrimination against staff had not been recorded or discussed at the weekly incidents meeting. It led to a conversation about how much staff were experiencing discrimination across the London Place without our knowledge. The hospice multidisciplinary team mobilised an anti-discrimination working group to drive change and increase staff support and safety. The working group co-designed a training programme incorporating real life scenarios and actors, to maximise session impact and learning. Aims: To increase London Place staff's confidence to 80% in challenging discrimination in the workplace by May 2022. To increase London Place staff's confidence to 80% in reporting discrimination in the workplace by May 2022. Methods: Utilising quality improvement methodology (Institute for Healthcare Improvement, 1991), the working group designed a survey which gathered baseline data and input from varying London Place staff grades. Responses helped to shape the training programme. A pilot session informed the working group of required adjustments following participant feedback. Seven training sessions were delivered in all via a mixture of face to face and online formats. Pre- and post- surveys were collected from participants to capture time series, quantitative, and qualitative data regarding staff confidence. Thematic and quantitative data analysis performed. Results: Aims of the project are on and exceeding target, overall staff confidence in reporting discrimination has risen to 83% and staff confidence in challenging discriminatory behaviour has risen to 80%. Process measure: number of discrimination incidents reported during training period. Outcome measures: pre- and post- training survey responses. Conclusion: Due to the success of the project, the organisation is adopting the locally developed anti-discrimination training as their standardised national training programme for anti-discrimination. Supporting their goal of becoming an 'anti-racist' organisation.